2009
DOI: 10.1080/02699200802716074
|View full text |Cite
|
Sign up to set email alerts
|

The effects of surgical rapid maxillary expansion (SRME) on vowel formants

Abstract: The objective of this study was to investigate the effect of surgical rapid maxillary expansion (SRME) on vowel production. The subjects included 12 patients, whose speech were considered perceptually normal, that had undergone surgical RME for expansion of a narrow maxilla. They uttered the following Turkish vowels, ([a], [e], [dotless i], [i], [o], [oe], [u], [y]), in isolation before and after the maxillary expansion. These samples were recorded for acoustical analysis. The fundamental frequencies (F0) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
2
8
0
1
Order By: Relevance
“…Our findings confirm other studies showing that placement of an orthodontic device causes an immediate reduction in fricative peak frequency. Both fricatives displayed this behaviour at RME placement, and then, the peak frequency gradually increased during therapy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings confirm other studies showing that placement of an orthodontic device causes an immediate reduction in fricative peak frequency. Both fricatives displayed this behaviour at RME placement, and then, the peak frequency gradually increased during therapy.…”
Section: Discussionsupporting
confidence: 92%
“…These significant changes in palatal morphology may affect speech by modifying the articulation sites of the tongue on the palate and changing the oral resonance mechanism by enlarging the oral cavity. A correct speech pronunciation is related to palate size, and maxillary surgical expansion causes vowel sound modification . The introduction of fixed elements in the oral cavity, such as an artificial palate or orthodontic appliances, alters consonant and vowel articulation …”
Section: Introductionmentioning
confidence: 99%
“…There are many studies 6,9,10,[20][21][22][23] whose authors have used subjective evaluation of the consonants and vowels and who have reported effects of the orthodontic application on the speech articulation in the literature, whereas fewer studies 13,[24][25][26][27] contained objective assessment of the formant frequencies.…”
Section: Effects Of Hawley Retainers On Speechmentioning
confidence: 99%
“…In addition, the authors found that the F 1 frequency of the vowel /i/ increased, whereas F 2 and F 3 decreased. Sarı et al 11 investigated the effect of surgical RME on vowel production. The F 2 frequency of the vowels /i/ and [oe] showed a decrease because the vowels were affected by the size of the anterior oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…F 1 values vary mostly with changes in tongue height, while F 2 varies mostly with changes in tongue advancement. 11 In 2005, Moura et al found an apparent increase in F 1 frequency among the RME group in their study of Down syndrome patients. According to the authors, this was explained by expansion of the airways caused by RME, enlargement of the vocal tract, and provision of enough space for the tongue.…”
Section: Introductionmentioning
confidence: 99%